Magnesium fluoride (MgF2) – A novel sintering additive for the preparation of transparent YAG ceramics via SPS - Nečina, Vojtěch; Hostaša, Jan; Pabst, Willi; Veselý, Martin (Journal of the European Ceramic Society, 2022)
The effect of MgF2 as a sintering additive for the preparation of YAG ceramics via spark plasma sintering (SPS) is investigated with promising results, as nearly complete densification (0.58% porosity) is achieved at relatively low temperature and moderate pressure. Higher temperature and dwell time resulted in a translucent/transparent body. On the other side, significant grain growth was observed with MgF2 addition.